Behcet's Disease: Is There Geographical Variation? A Review Far from the Silk Road - Leonardo, Nieves Marie (Int J Rheumatol, 2015)
Behcet's Disease (BD) is a systemic vasculitis characterized by the triad of recurrent mouth and genital ulcers with eye involvement. To date there are no laboratory tests specific for the disease and diagnosis continues to remain on clinical grounds. Multiple criteria have been created as guides for diagnosis; however, given the wide spectrum of organ involvement, some cases remain undiagnosed. The diagnosis of Behcet's Disease may only be made over time as the clinical manifestations emerge sometimes separated by months and even years. With an increased recognition of this disease it has become apparent that there is geographical variation in clinical manifestations. In particular cardiac manifestations are not seen commonly in Caucasians compared to Asian and Middle Eastern patients, while neurological manifestations are more common in Caucasians. Use of immunosuppressive and immunomodulatory drugs to suppress inflammation remains the cornerstone of treatment.